PREVALENCE RATE AND CAUSES OF LEPTOSPIROSIS SEROVAR ON CATTLE AT GIWANGAN’S ABATTOIR OF YOGYAKARTA - Steffanie Merlin Clyricia Noach; Yakob Robert Noach (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2020)
Leptospirosis is a zoonotic disease caused by Leptospira bacteria. The disease was spreadout arround the world, especially in the tropical and subtropical regions included Indonesia. The International Leptospirosis Society has established Indonesia is the country with high incidence of leptospirosis. Daerah Istimewa Yogyakarta is one of the regions in Indonesia with endemic of leptospirosis. Leptospirosis infection in humans can occur through direct or indirect contact with the urine of infected animals. Cattle is one of the source of transmission leptospirosis to human and other animals. The purpose of this study was to determine the prevalence rate of leptospirosis and identify serovar caused of leptospirosis in cattle at Giwangan’s abattoir Yogyakarta. Blood collection taken from ten heads of cattle via jugular vein and the serum was separated for leptospirosis examination by Microscopic Aglutination Test (MAT) which taken placed at Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP), Salatiga. Microscopic Aglutination Test carried out on various Leptospira serovar, namely: Bangkinang, Canicola, Pyrogenes, Robinsoni, Hardjo, Djasiman, Grippotyphosa, Hebdomadis, Icterohaemorragie, Pomona, Bataviae, Rama, Mini, Sarmin and Manhao. The prevalence rate detemine by compared between the number of MAT positive and samples examined. Positive agglutination indicated the serovar types that caused leptospirosis in cattle. The results showed that two samples were positive against antigen serovar Grippotyphosa (1/2), Hebdomadis (2/2) dan Mini (1/2). It can be concluded that the prevalence rate of leptospirosis in cattle at Giwangan’s abattoir Yogyakarta were 20%. The cause of leptospirosis in cattle at Giwangan’s abattoir Yogyakarta namely Leptospira interrogans serovar Grippotyphosa, Hebdomadis and Leptospira borgpetersenii serovar Mini.